Analysis on sound absorber panel made of oil palm Mesocarp Fibre using Delany-Bazley and Johnson-Champoux-Allard models - Abdul Latif, Hanif; Zaman, Izzuddin; Yahya, Musli Nizam; Sambu, Mathan; Meng, Qingshi (Penerbit UNIMAP, 2020)
Oil palm mesocarp fibre is seen as one potential of reinforcement in polymers due to its high strength, low cost, environmentally friendly nature and availability. Recently, it has attracted greater interest from academia and industries due to its potential for making a low-cost sound absorption panel. Therefore, this study is obliged to investigate the acoustic characteristics and the physical properties of oil palm mesocarp fibre (OPMF) as a porous material for sound absorbing panel. The measurements of the sound absorption coefficient are determined by using: (1) analytical model of Delany-Bazley, (2) analytical model of Johnson-Champoux-Allard, and (3) experiment of the impedance tube method. A commercial polyurethane (PU) was used as a composite binder during the intermixing process with the fibres. The manufacturing parameters are 10/90, 20/80, 30/70 and 40/60 by wt.% of PU/OPMF. The outcome shows that adding binder compacts the fibre by reducing the pore diameter and porosity, thus increasing the flow resistivity. Results also indicate that Johnson-Champoux-Allard model can justify the overall trend of absorption of the coefficient perfectly in contrast to the Delany-Bazley model. Overall, OPMF with 10 wt.% PU binder displayed greater absorption from low to mid-frequency range and the highest value of noise reduction coefficient of 0.66, while fibres with 20 wt.% PU produced the highest value of sound absorption coefficient of 0.99 at 1000 Hz. The results conclude that oil palm mesocarp displays a potential and brighter prospect to be implemented as a sound absorption panel as demonstrated in this study.